Penguatan Pengelolaan Badan Usaha Milik Desa (BUMDes) Sebagai Penggerak Ekonomi Masyarakat di Desa Jatirejo Kecamatan Lendah Kabupaten Kulon Progo - Fitri Rahmawati; Titin Ekowati; Ira Haryani (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
This community service program assists the management of the Village-Owned Enterprise (BUMDes) in Jatirejo Village, Lendah District, Kulon Progo Regency, and provides training in institutional management and entrepreneurship to support the economy of the Jatirejo Village community in improving organizational performance optimally and effectively. This community service program will be implemented by providing outreach and support to BUMDes administrators in Jatirejo Village. The service implementation methodology is carried out in three phases: an introduction phase to identify partner locations, an implementation phase to contact partners and conduct training activities, and an evaluation phase to determine how well this is being done. The training activities can be attended by BUMDes stakeholders. The material provided discusses the role of BUMDes as a driver of the economy, organization, and entrepreneurship. It is hoped that this PKM activity will provide knowledge to BUMDes administrators in Jatirejo Village and will build the role of BUMDes as a driving force for the village economy, organizational management and entrepreneurship formation. The results of this community service program are also expected to serve as a basis for the government to formulate policies and programs related to BUMDes development issues.